The Impact Of Job Design, Conflict And Workplace Stress On Elementary Theacher’s Job Performance - M J Renwarin, Joseph (International Journal of Educational Research & Social Sciences, 2021)
This research aims to understand job performance of elementary teachers. This research is a explanatory and evaluative research. The researcher want to know and analyze what are the impact of job design, conflict and stress to job performance. This research samples are 156 respondents with purposive samping method. The researchers use questionnaires disbursement by grouping of area. Data Calculation, For the relationship between two variables and analyze by Statistical Package for the Social Sciences (SPSS) software 22.0 version. All the variables as simultan and together had impact to job performance. Eventhough the results of research is all the variables have influence significants but there are some interesting points of view of this research result.